Diplomats' Wives and the Foreign Ministry in Late Imperial Russia, in Four Portraits. Issue 1 (1st June 2022) - Soroka, Marina
Abstract: The infrequent publications about women's agency in European diplomacy have concerned themselves with either the early modern age or the post-World War I period, but women remain virtually absent from the diplomatic history of the long nineteenth century. To determine their place in the European political world of this period, this article examines the experiences of four Russian diplomats' wives. The biographical approach reveals contradictions in patriarchal discourse: it required a diplomat's wife to be worthy of her role as a representative of the Russian Empire, yet effectively dismissed her from politics. From this another contradiction ensued: as a diplomat's wife played no political role, the ministry turned a blind eye if her actions challenged traditional social and gender norms, even when such actions led to the neglect of her duties as her husband's helpmeet.